Correlation between Soil Test Phosphorus of Kaolinitic and Smectitic Soils with Phosphorus Uptake of Lowland Rice - Mohammad Masjkur (UNIVERSITY OF LAMPUNG, 2009)
Correlation between soil test phosphorus (P) and plant-available P parameters were affected by soil properties, such as soil pH, particle-size composition, and mineralogy. The objectives of this research were: (1) to determine P concentration extracted by several soil P test method in kaolinitic and smectitic soil, and (2) to determine correlation between soil P test and soil properties, P fractions, P sorption parameters, and P uptake of lowland rice. The soil P test in kaolinitic and smectitic soil used solutions of HCl 25%, Truog, Olsen, Bray1, Mehlich1, and Morgan Venema and were correlated with P uptake of lowland rice in field experiment. Concentration of Truog-P in kaolinitic soil was significantly higher than smectitic soil, while concentration of Morgan-P in kaolinitic soil was significantly lower than smectitic soil. Concentration differences of HCl 25%-P, Olsen-P, Bray1-P, and Mehlich1-P between kaolinitic and smectitic soil were not significant. In kaolinitic soil correlation between HCl 25%-P, Olsen-P, Bray1-P, and Mehlich1-P, and Morgan-P with P uptake of lowland rice were not significant. In smectitic soil HCl 25%-P, Olsen-P, Bray1-P, and Mehlich1-P correlated significantly with P uptake of lowland rice, while Morgan-P was not significant.